(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Delirium is a syndrome characterized by the rapid onset of variable and fluctuating changes in attention resulting in disturbed behavior, illusions, hallucinations & changing level of consciousness caused by physiological consequences of a medical disorder, its prevalence is estimated to be bout 15-20% of general medical wards. Objectives: The aim of this study is to measure the prevalence of delirium in patients admitted to medical wards and to study signs and symptoms of delirium. Methods: A cross sectional study of all patients who were admitted to the medical wards of Al-Kadhimiya Teaching Hospital in Baghdad during the study period which is from 21 March 2008 to 21 April 2008, the total admissions were 510 patients, with excluding criteria: a pre-existing psychiatric disorder and age less than 18 year. - Approval to the questionnaire was taken from the relatives. - All patients with delirium were referred by residents during the study period - Delirium cases were diagnosed according to DSM IV criteria; prevalence was estimated and symptoms studied Results: The prevalence of delirium was about 3% among the medical inpatients. Conclusion: The prevalence of delirium reported in this study is low in comparison to other studies. This is explained in terms of difference of methodology used in this study in comparison with other studies. Key words: delirium, inpatients, medicine